2016
DOI: 10.1177/0363546516673837
|View full text |Cite
|
Sign up to set email alerts
|

Two-Year Outcomes of a Randomized Trial Investigating a 6-Week Return to Full Weightbearing After Matrix-Induced Autologous Chondrocyte Implantation

Abstract: Patients in the AR group who reduced the length of time spent ambulating on crutches produced comparable outcomes up to 24 months, without compromising graft integrity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
94
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(94 citation statements)
references
References 52 publications
(89 reference statements)
0
94
0
Order By: Relevance
“…This included 127 patients undergoing TF MACI to the medial (MFC) and lateral A power calculation was performed using G-Power (Dusseldorf, Germany) for the primary outcome variable (MRI composite score), demonstrating that 38 patients were required in each group to reveal differences at the 5% significance level, with 90% power and employing an effect size of 0.76 based on previous research. 13 All patients provided their written informed consent prior to study enrolment and pre-operative clinical evaluation, and ethics approval was obtained from the relevant hospital ethics committee. The magnetic resonance observation of cartilage repair tissue (MOCART) scoring system was employed to assess eight different parameters of graft repair, including graft infill, signal intensity, border integration, surface contour, tissue structure, subchondral lamina, subchondral bone and effusion.…”
Section: Introductionmentioning
confidence: 99%
“…This included 127 patients undergoing TF MACI to the medial (MFC) and lateral A power calculation was performed using G-Power (Dusseldorf, Germany) for the primary outcome variable (MRI composite score), demonstrating that 38 patients were required in each group to reveal differences at the 5% significance level, with 90% power and employing an effect size of 0.76 based on previous research. 13 All patients provided their written informed consent prior to study enrolment and pre-operative clinical evaluation, and ethics approval was obtained from the relevant hospital ethics committee. The magnetic resonance observation of cartilage repair tissue (MOCART) scoring system was employed to assess eight different parameters of graft repair, including graft infill, signal intensity, border integration, surface contour, tissue structure, subchondral lamina, subchondral bone and effusion.…”
Section: Introductionmentioning
confidence: 99%
“…In the current study, the overall satisfaction rate (81%) is comparable to prior reports though satisfaction scores varied by procedure. In particular, cartilage restoration patients had lower satisfaction scores at the time of rehabilitation completion; this may be related to a longer time interval of up to two years before knee symptoms are maximally improved, 24 , which is substantially longer than the active postoperative rehabilitation period. 24 Ardern et al report a satisfaction rating of 72% after primary ACL reconstruction.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, cartilage restoration patients had lower satisfaction scores at the time of rehabilitation completion; this may be related to a longer time interval of up to two years before knee symptoms are maximally improved, 24 , which is substantially longer than the active postoperative rehabilitation period. 24 Ardern et al report a satisfaction rating of 72% after primary ACL reconstruction. 3 Partial meniscectomy satisfaction has been reported around 83%.…”
Section: Discussionmentioning
confidence: 99%
“…A randomized trial of 6 week versus 8 week return to full weight bearing found no significant difference in failure rates or symptom improvement at 2 years (interim 12-month results reported in an earlier publication [19]); the study authors concluded accelerated weight bearing after MACI is safe [20]. Another trial of 6 week versus 10 week return to full weight bearing with 5 years follow-up after MACI similarly found no difference in symptom improvement between groups [21].…”
Section: Cartilage Repair and Regenerationmentioning
confidence: 95%